The dental monomer HEMA causes proteome changes in human THP‐1 monocytes. Issue 4 (11th January 2019) - Samuelsen, Jan Tore; Michelsen, Vibeke Barman; Bruun, Jack‐Ansgar; Dahl, Jon E.; Jensen, Einar; Örtengren, Ulf
Abstract: Resin‐based biomaterials are widely used in medical and dental treatment, and both clinicians and patients are exposed to the materials. The knowledge of toxicity is mainly based on in vitro studies at exposure concentrations that induce cell death. However, severe cell damage and cell death signaling may overshadow essential cellular events caused by a possible toxicant. For dental resins, the knowledge of interaction with living cells at more clinical relevant exposure doses is sparse. 2‐Hydroxyethylmethacrylate (HEMA) is a commonly used monomer in dental resins. Measuring cellular adaptation to HEMA at concentrations that did not reduce cell viability was the main focus of this study. Stable isotope labeling with amino acids in cell culture was used to measure proteome changes in cultured THP‐1 cells exposed to HEMA. Western blotting verified the results. Cells exposed to HEMA increased their level of several cytoprotective proteins. The observed adaptation is compatible with increased oxidative burden caused by GSH depletion and the electrophilic characteristic of HEMA. The present approach to analyzing the toxic potential of HEMA yielded information on interactions with living cells is not previously reported. This detailed information is of great value to make better predictions of possible side effects in the clinic. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 107A: 851–859, 2019.